Regarding the Ecuadorian indigenous movement in the last decade of the 20th century - Ismodes Alegría, Julio César (2007)
From 1990 to 2000, Ecuadorian indigenous peoples were the protagonists of a social and political movement that managed to participate in the forefront of the struggle for power. For the first time, thousands of community members forced the authorities to recognize them and negotiate directly with them; at the climax one of its leaders was incorporated into the top of the government. The author exposes the background, rebellion describes it as indigenous, discusses its cultural characteristics, raises the challenges that remain pending to achieve an inclusive society, perhaps the most important challenge faced by Latin American societies with a significant indigenous population and history.